Evaluation of the host immune response to decellularized lung scaffolds derived from α-Gal knockout pigs in a non-human primate model. (December 2018) - Stahl, Elizabeth C.; Bonvillain, Ryan W.; Skillen, Clint D.; Burger, Brandon L.; Hara, Hidetaka; Lee, Whayoung; Trygg, Cynthia B.; Didier, Peter J.; Grasperge, Brooke F.; Pashos, Nicholas C.; Bunnell, Bruce A.; Bianchi, John; et al.
Abstract: Whole organ tissue engineering is a promising approach to address organ shortages in many applications, including lung transplantation for patients with chronic pulmonary disease. Engineered lungs may be derived from animal sources after removing cellular content, exposing the extracellular matrix to serve as a scaffold for recellularization with human cells. However, the use of xenogeneic tissue sources in human transplantation raises concerns due to the presence of the antigenic Gal epitope. In the present study, lungs from wild type or α-Gal knockout pigs were harvested, decellularized, and implanted subcutaneously in a non-human primate model to evaluate the host immune response. The decellularized porcine implants were compared to a sham surgery control, as well as native porcine and decellularized macaque lung implants. The results demonstrated differential profiles of circulating and infiltrating immune cell subsets and histological outcomes depending on the implanted tissue source. Upon implantation, the decellularized α-Gal knockout lung constructs performed similarly to the decellularized wild type lung constructs. However, upon re-implantation into a chronic exposure model, the decellularized wild type lung constructs resulted in a greater proportion of infiltrating CD45 + cells, including CD3 + and CD8 + cytotoxic T-cells, likely mediated by an increase in production of Gal-specific antibodies. The results suggest that removal of the Gal epitope can potentially reduce adverse inflammatory reactions associated with chronic exposure to engineered organs containing xenogeneic components.